THE EFFECTIVENESS OF MOBILIZATION IN IMPROVING MOTHER'S FUNCTIONAL STATUS AFTER CAESAREAN SECTION DELIVERY - Razan, Aqmarina; Wijianto, W (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Over the past 30 years, the incidence of cesarean section or sectio caesarea (SC) has increased. One of the complications of SC is postoperative pain. Pain can interfere with the patient's quality of life and reducing mother’s the functional status. One of the physiotherapy management that can be done is mobilization. Case Presentation: A 28-year-old pregnant woman came to Hospital in Madiun, East Java, Indonesia with complaints of ruptured membranes and breech presentation. The doctor performed a cesarean section (SC) operation on the patient. After SC the patient complained of pain at the incision site. Postoperatively the patient was in bed with an IV and catheter attached. The patient's vital signs are normal. Management and Outcome: The patient was mobilized for 2 days. This mobilization can be divided into 3 stages. The first stage (0-8 hours postoperatively) the patient sits on the edge of the bed, proceeds to get out of bed then sits in a chair and ambulates according to the patient's tolerance, the second stage (8-24 hours postoperatively) Ambulates according to the patient's tolerance, continues walking 1- 2 minutes (or more), third stage (24-48 hours postoperatively) Walk down the hall 3-4 times (or more), then get out of bed every 8 hours. Discussion: Mobilization has a good impact on patients after cesarean delivery. Ambulation helps reduce most of the complications by ensuring good blood circulation, improving breathing, and increasing physical strength. This is proven by an increase in the patient's Katz index, where the C score changes to A after mobilization Conclusion: Exercises given after cesarean delivery can increase transfer and ambulation activities from sleeping to sitting, sitting independently, sitting to standing, standing independently, and walking independently.